Peningkatan Hasil Belajar Sepak Bola Melalui Pendekatan Scientific Dalam Pembelajaran Penjasorkes - Rangga, Geni (Department of Physical Education, Sport, Health and Recreation, 2016)
The purpose of the study is the improvement of football studies result through scientific approachin Physical teaching and learning in V grade of SD N Kemantran 01 Tegal academicyear 2015. This study use classroom action research that consist of two cycle, each cycle last forone meeting. Each cycle consists of four steps, namely, planning, implementation, observationand reflection. The result of the first cycle showed that students? result of study haven?t achivethe standart minimum yet. From 41 students, only 30 students that can achieve the standartminimum in football learning through Scientific Appoach with the percentage 73%. Furthermore,on the second cycle there was an improvement that 88% or 36 students can achieve standartminimum in football learning through Scientific Approach. Based on the result, it wasconclude that there was an improvement of football studies result through scientific approachin penjasorkes learning in V grade of SD N Kemantran 01 Tegal.